The “Rustam and Isfandiyar” in the poem of “Shahnameh” - Kudaybergenova, G. K. (Journal of Oriental Studies, 2016)
In this article, we briefly discuss about episode dedicated to “Rustam and Isfandiyar” from Firdausi’s well-known poem “Shahnameh”. In addition, we consider the battle between the young Iranian knight and an experienced hero.